2020
DOI: 10.1177/1359104520914695
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Mutism Questionnaire: Data from typically developing children and children with selective mutism

Abstract: The core symptom of the anxiety disorder selective mutism (SM) is absence of speech in specific situations, such as at school. The most commonly used standardized instruments to assess speaking behavior are the parent-rated Selective Mutism Questionnaire (SMQ) and the teacher-rated School Speech Questionnaire (SSQ), scored from 0 to 3, indicating that speaking behavior never, seldom, often, and always occur. They were developed to assess severity of mutism and potential effects of treatment. However, prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 30 publications
2
29
0
2
Order By: Relevance
“…Before addressing the main results of the present study, a number of general findings are reported. First, a comparison of the SMQ, PAS-R, ASQ, and BIQ-SF scores with normative data of these measures (Spence et al, 2001;Vreeke et al, 2012;Van der Ploeg and Scholte, 2014;Oerbeck et al, 2020) revealed that parents rated the children in the present study as clearly falling in the normal range of selective mutism, social anxiety, autistic features, and behavioral inhibition. Second, demographic variables did not have a significant influence on the constructs that were assessed in this study.…”
Section: General Findingsmentioning
confidence: 74%
See 1 more Smart Citation
“…Before addressing the main results of the present study, a number of general findings are reported. First, a comparison of the SMQ, PAS-R, ASQ, and BIQ-SF scores with normative data of these measures (Spence et al, 2001;Vreeke et al, 2012;Van der Ploeg and Scholte, 2014;Oerbeck et al, 2020) revealed that parents rated the children in the present study as clearly falling in the normal range of selective mutism, social anxiety, autistic features, and behavioral inhibition. Second, demographic variables did not have a significant influence on the constructs that were assessed in this study.…”
Section: General Findingsmentioning
confidence: 74%
“…To enhance interpretability, the main analyses were conducted using a reversed SMQ total score for which higher scores reflect higher symptom levels of SM. Previous studies have shown that the SMQ is a reliable scale (with Cronbach's in the 0.80 to 0.90 range) that relates in a theoretical meaningful way with other measures (Bergman et al, 2008;Letamendi et al, 2008), predicts the diagnostic status of SM (Oerbeck et al, 2020), and is sensitive to document treatment effects (Bergman et al, 2013;Oerbeck et al, 2015).…”
Section: Assessmentmentioning
confidence: 99%
“…Selective Mutism In a medical history sheet the mothers of the children with SM first made some demographic statements and gave information on the child`s course of SM (Melfsen 2014). Symptoms of SM, its severity, scope and functional impairment were assessed by the German version of the parent report ‘Selective Mutism Questionnaire’ (SMQ) (Bergman et al 2008 ; Letamendi et al 2008 ; Oerbeck et al 2020 ). The SMQ is a 17-item parent-rating measure designed to assess the severity of SM.…”
Section: Methodsmentioning
confidence: 99%
“…Second, researchers have developed psychometrically sound measures of selective mutism (Oerbeck et al, 2020). These measures include the Selective Mutism Questionnaire (SMQ; Bergman et al, 2008), the School Speech Questionnaire (SSQ; Bergman et al, 2002), and the Strong Narrative Assessment Procedure (SNAP; Strong, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The SMQ is a 17‐item parent‐report that measures a child's speaking behavior across three subscales (home, school, other). Parents are asked to rate their child's frequency of speech on a scale from 0 ( Never ) to 3 ( Always ) on items such as “When appropriate, my child talks to most peers at school.” The SMQ has been found to have good reliability, convergent and discriminant validity, and sensitivity to treatment‐related change, with internal consistency ranging from α = .78 to .97 (Bergman et al, 2008; Letamendi et al, 2008; Oerbeck et al, 2020).…”
Section: Introductionmentioning
confidence: 99%